2017
DOI: 10.1186/s12906-017-1770-8
|View full text |Cite
|
Sign up to set email alerts
|

"Placebo effect is probably what we refer to as patient healing power": A qualitative pilot study examining how Norwegian complementary therapists reflect on their practice

Abstract: BackgroundComplementary therapists spend considerable time with their patients, especially in the first consultation. The communication between patients and their therapists is important for raising consciousness and activation of the patient’s self-healing power. Thus, the aims in this study were to delineate what complementary therapists regard as essential in patient consultations, their view of the healing process, and how the therapists understand the placebo effect and its position in the healing process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 33 publications
(39 reference statements)
0
34
0
Order By: Relevance
“…This study found that the patients’ positive beliefs and expectations about the treatment play a significant role in the self-healing process. The CAM providers understood placebo effect as the patient’s self-healing power, resulting from establishing trust and belief in the treatment process [30]. Moreover, the therapist–patient relationship becomes more equitable if both parties respect one another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the patients’ positive beliefs and expectations about the treatment play a significant role in the self-healing process. The CAM providers understood placebo effect as the patient’s self-healing power, resulting from establishing trust and belief in the treatment process [30]. Moreover, the therapist–patient relationship becomes more equitable if both parties respect one another.…”
Section: Discussionmentioning
confidence: 99%
“…According to Helman [29], curing and healing are both included in practical clinical work. CAM therapists, as opposed to doctors, often spend more time with their patients [30]. This enables them to maintain the emotional aspects to a greater extent, which makes the patients feel like whole persons rather than purely biological phenomena.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…A systematic review by Colagiuri and Smith [ 15 ] demonstrated a significant association between patients’ expectancies and acupuncture treatment outcomes, and, as to alternative therapists, they did indeed appreciate the placebo effect as part of treatment outcome. Patients’ expectancy, modulated by contextual setting and patients’ experience during the therapy, is considered crucial to a successful treatment [ 16 ]. This notion may also be applied to parents, as their expectancy also plays an important role [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The features that characterize many CAM practices, the conditions CAM clients tend to seek help for, as well as the comments of both practitioners and clients, all suggest that this may be the case. While it is difficult to make generalizations with regards to CAM treatments, given their number and diversity, features that are common to many of these practices include long consultations, expressions of warmth and empathy from practitioners, time devoted to the mutual development of explanation, as well as the instillation of hope (Carter, 2003;Ernst, 2001;Kaptchuk & Eisenberg, 1998;Stub, Foss, & Liodden, 2017). These features are known to increase placebo responses across a variety of conditions (Friesen & Blease, 2018;Howe, Goyer, & Crum, 2017;Kaptchuk et al, 2008).…”
Section: Today's Mesmerism? Complementary and Alternative Medicinementioning
confidence: 99%
“…Finally, interviews with CAM practitioners and clients reveal that aspects of these treatments that are likely to enhance placebo responses are often seen as central to the practices (e.g. understanding and explanation, holistic care, a meaningful therapeutic alliance, belief in the treatment) (Astin, 1998;Sirois, Salamonsen, & Kristoffersen, 2016;Stub et al, 2017).…”
Section: Today's Mesmerism? Complementary and Alternative Medicinementioning
confidence: 99%